Hubungan Kontrol Diri dengan Perilaku Merokok Remaja di Kelurahan Dendengan Dalam Kota Manado - Datangmanis, Novelya Friska; Simak, Valen Fridolin; Rompas, Sefty Jehermia (Mapalus Nursing Science Journal, 2023)
Background: Low self-control in adolescents results in inability to direct and regulate their behavior. Consequently, this causes uncontrolled behavior such as smoking. Objective: The objective of this study to determine the relationship between self-control and adolescent smoking behavior in Dendengan sub-district, Manado. Method: This research was a quantitative research with a cross sectional approach. A total of 201 respondents participated in this study. The questionnaires used in this study were self-control scale questionnaires and smoking behavior questionnaires. Data analysis utilized chi square test. Results: The study showed a value of p = 0.000 (p = 0.000 or p <0.05) meaning that the higher the self-control of adolescents the lower the smoking behavior. Discussion: Self-control is related to smoking behavior in adolescents because adolescents who have good self-control will control their behavior in determining actions such as smoking behavior. Conclusion: There is a relationship between self-control and adolescent smoking behavior in Dendengan sub-district, Manado.